Factors Affecting for Using Services of Mobile Phone Network for Customer of the Lao Telecommunications Company, Oudomxay Province: https://doi.org/10.69692/SUJMRD100456 - KINGSAKDA, VONGKEO; DUANGVILAYKEO, Thipphavanh; SAYBOUNHEUANG, Saythala (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
The purpose of this study was 1) to study the situation of customers using mobile phone network services of Lao Telecommunications Company, 2) to study the significant between customers and the mobile network of Lao Telecommunications Company, 3) to findout the factors affecting customer's loyalty to the mobile phone network service of Lao Telecommunication Public Company. It was a quantitative research with the target group being customers who use the service through the mobile phone network of customers of Lao Telecommunications Company in Uodomxay province, used 402 sample group and questionnaires were used to collect data and analyzed the data by using SPSS program. The results found that most of the users of the Lao Telephony network service were using the Internet (Data), spending 50,000-100,000 kip per month, the period of using the number is more than 2 years. The important aspects in making a relationship with Lao Telecom customers are marketing promotion, service process, customer monitoring, administration, communication between customers, and partnership which are in the high level. Factors affecting customers' loyalty to Lao Telecommunication Public Company's mobile network services include repeat service use factors, referral factors, and non-switching network factors with a statistical significance level of 0.01.